PERAN DIVERSITY PROJECT DALAM MEMPERSATUKAN KEBERAGAMAN INDONESIA DI ERA GLOBALISASI - Hendi Sama; Dame Afrina Sihombing; Teddy Jurnali; Putri Salsabella; Elita Elita; Nindi Suci Rahmadani; Nur Alficha; Silfia Nadilla; Febby Febby; Kezia Yohana Zai; Surya Chandra; Tuanku Stefino (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
In the current era of globalization, it is very rare to find people who live in harmony with the diversity that surrounds them. As we know, developments in the current era of globalization have not been spread evenly and have not been done well. There are some people who might still not be able to understand the diversity and reversal that we must unite so that Indonesia is not divided as our motto,